Şirketlerin Hayatta Kalma Kabiliyetleri: İMKB Örneği (Survival Ability of Firms: The Case Of ISE) - Hakan ALTIN; Mehmet Emin KARABAYIR; Cemil SÜSLÜ (Dokuz Eylül Üniversitesi Sosyal Bilimler Enstitüsü Dergisi, 2010)
The crisis taking place in the financial markets inevitably affects the reel sector. Survival of the firms during or after the crises is closely related to their debt structures and operational decisions. In this respect, consistency between debt/equity structures and operational decisions of the listed companies is crucial in terms of their survival-ability, particularly during the crisis periods.This paper examines survival ability of the 142 firms registered to the İstanbul Stock Exchange (ISE) Industrial Index both before and after the crisis. Constant returns to scale approach is used in the analysis. While the input variables used are related to the financial structures of the firms, the output variables refer to the operational structures of the firms. Of the 136 firms from the sample whose analyzable data was accessed, 18 are found to be relatively efficient before the crisis. The number of relatively efficient firms rises to 24 after the crisis. This situation leads to a conclusion that the firms registered to ISE Industrial Index are vulnerable in terms of debt management.